The role of consulting serrvices in promoting competitive culture - Caraganciu, Anatolie (Mednarodno inovativno poslovanje, 2019)
Maintaining a normal competitive environment on the market is the core objective of the competition authorities. Policies and regulations applied in pursuit of this purpose have the role of identifying and eliminating situations of constraint on free competition. The developing market of Moldova is characterized by a low level of the competitive culture. Therefore, the business community have few knowledge and understanding of competition policies and regulations, relatively new in this market. In other cases, the lack of cooperation with competition authorities leads to erroneous information and ineffective decisions.
Keywords: competition advocacy; competititive culture; consulting services; konkurenčna kultura; svetovalne storitve; zagovorništvo konkurence